PERSEPSI MAHASISWA AA YKPN TERHADAP BANK SYARIAH - Evi Grediani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2016)
This research aims to find out the perception of accounting students to Syariah Banking. The subject in this research is a student of YKPN Accounting Academy, Yogyakarta. One Hundred subjects participated in the quesionaire survey. Subjects are randomly assign. Analysis unit was students who had the use of syariah banking and methods of data analysis was validity analysis, reability analysis and regression analysis. The results show the following that the accounting students of YKPN Academy had good (positive) perception to Syariah Banking. Key words: Syariah Banking, Perception